Economic knock-on effects of Russia's geopolitical risk on advanced economies: A global VAR approach - Boris Blagov; Maximilian Dirks; Michael Funke (RWI - Leibniz-Institut für Wirtschaftsforschung, 2024)
Using Russia as a case study and a global VAR model as a methodological tool, we analyze how heightened geopolitical risk shocks propagate across advanced economies and quantify the economic effects of these events. The global VAR impulse response functions in response to the skyrocketing Russian geopolitical risk shock after Russia's invasion of Ukraine revealed a contraction of GDP and an increase in inflation. Eastern European neighboring countries are particularly affected by the Russian geopolitical risk shock. We also document a strong component of the Russian geopolitical risk shock that is not driven by fossil fuel prices. – – Unter Verwendung des Fallbeispiels Russland und eines globalen VAR-Modells als methodisches Instrument analysieren wir, wie sich Schocks eines erhöhten geopolitischen Risikos in fortgeschrittenen Volkswirtschaften verbreiten und quantifizieren die wirtschaftlichen Auswirkungen dieser Ereignisse. Die globalen VAR-Impuls-Antwort-Funktionen als Reaktion auf den sprunghaften Anstieg des geopolitischen Risikos in Russland nach dem Einmarsch in die Ukraine zeigen einen Rückgang des BIPs und einen Anstieg der Inflation. Staaten in Osteuropa sind von diesem geopolitischen Risikoschock in Russland besonders betroffen. Ein Großteil der beobachteten Effekte wird nicht durch Energiepreise getrieben.
Keywords: C32; E32; F51; F52; 330; Geopolitical risk; international business cycle transmission; global VAR model; Russia